2020
DOI: 10.3389/fgene.2020.00905
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KIF18B as a Hub Candidate Gene in the Metastasis of Clear Cell Renal Cell Carcinoma by Weighted Gene Co-expression Network Analysis

Abstract: Background: Clear cell renal cell carcinoma (ccRCC) is a common type of fatal malignancy in the urinary system. As the therapeutic strategies of ccRCC are severely limited at present, the prognosis of patients with metastatic carcinoma is usually not promising. Revealing the pathogenesis and identifying hub candidate genes for prognosis prediction and precise treatment are urgently needed in metastatic ccRCC. Methods: In the present study, we conducted a series of bioinformatics studies with the gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…The other method was Maximal Que Centrality (MCC) algorithm [ 44 ] from plug-in cytoHubba in Cytoscape (Version 3.6.0) software [ 45 ]. The top ten genes ranked by MCC values were considered as hub candidates [ 46 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The other method was Maximal Que Centrality (MCC) algorithm [ 44 ] from plug-in cytoHubba in Cytoscape (Version 3.6.0) software [ 45 ]. The top ten genes ranked by MCC values were considered as hub candidates [ 46 , 47 , 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…KIF18B, a member of kinesin superfamily, has a long-reported significant effect on the onset and progression of cancer. 23 , 24 Wang et al 25 have identified KIF18B as a risk gene in the metastasis of ccRCC. HJURP, a histone H3 chaperone, was identified as a crucial factor in DNA binding and phosphorylation, which promotes chromosome segregation and cell mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we conducted module analysis using cythubba with the Maximal Que Centrality (MCC) method in Cytoscape (Version 3.7.2) [ 63 ]. The top ten genes ranked by MCC values were considered as hub candidates [ 64 , 65 , 66 , 67 ]. The overlapped candidates obtained from the two methods were identified as the hub genes.…”
Section: Methodsmentioning
confidence: 99%